[3,3]- and [5,5]-Sigmatropic Rearrangements of Aryl Sulfoxides Using An ‘Assembly/Deprotonation’ Technology - Zhang, Lei; Hu, Mengjie; Peng, Bo (Synlett, 2019)
The redox-neutral ortho-functionalizations of aryl/heteroaryl sulfoxides via interrupted Pummerer processes have been greatly advanced since its discovery by Kita and Padwa in the early 2000s. In this context, we recently developed an ortho-cyanoalkylation of aryl sulfoxides with alkyl nitriles using an ‘assembly/deprotonation’ protocol. The success of the reaction hinges on the independent control of the electrophilic assembly of both coupling partners and subsequent deprotonation of the in situ generated imine sulfonium intermediates. Further [3,3]-sigmatropic rearrangement of the in situ formed ketenimine sulfonium species furnishes ortho-cyanoalkylated aryl sulfides. More recently, we also applied the ‘assembly/deprotonation’ strategy for the development of the [5,5]-sigmatropic rearrangement of aryl sulfoxides with allyl nitriles that allows for para-cyanoalkylation of aryl sulfoxides. The development of these two reactions is described in this Synpacts article.1 Background2 [3,3]-Sigmatropic Rearrangement3 [5,5]-Sigmatropic Rearrangement4 Conclusion
Keywords: sigmatropic rearrangement; electrophilic activation; sulfoxides; cyanoalkylation; sulfur chemistry